Development of Natural Castile Soaps from Vegetable Oils - Abdulkerim Bilginer; Kadri Gökhan Özokan (Experimed, 2024)
Objective: Castile soaps are believed to be natural, 100% biodegradable, non-toxic surfactants and in some cases, they have antimicrobial properties. As raw materials, they are used extensively in the cosmetic industry for personal and home care products. Natural castile soap bases are generally produced in super fat stoichiometry to protect skin from caustic damage. The super fat method optimizes the total amount of caustic required for the saponification of natural vegetable oils and keeps these oils at the maximum level in the final product. The aim of this study was to develop natural soap based raw materials and castile soaps from various vegetable oils such as olive oil, coconut oil, castor oil, almond oil and jojoba oil.Materials and Methods: Castile soaps were produced using the super fat method by measuring the saponification values of the vegetable oils. Viscosity, pH, appearance, and microbiological tests were performed to determine their shelf life.Results: The castile formulations did not contain any preservatives, no microbiological risk was observed during their shelf life. All soap based raw materials and castil formulations have a two-year shelf life. These castile soaps are 100% soluble in water.Conclusion: This article documents the laboratory-scale production of six soap based raw materials and the development of five castile formulations for personal and household cleaning. Super fat method optimized the total amount of caustic required for the saponification of natural vegetable oils such as olive oil, coconut oil, castor oil and maintains the oils in the product at the maximum level without allowing the presence of free caustic in the final product. Super fat castile soaps are the safest personal and household cleaning products because they don’t contain caustic residue, have their long shelf life and feature high solubility in water minimizing the risk of residue on skin and surface.